Bio-based ultraviolet curing resin based on rosin as well as preparation method and application of bio-based ultraviolet curing resin
By using rosin-based bio-based materials and combining hydroxyacrylate synthesis technology, bio-based ultraviolet curing resin with high mechanical properties and environmental protection characteristics is prepared, which solves the dependence on non-renewable resources and environmental pollution in the prior art. Problem, the preparation of high-performance environmentally friendly materials has been achieved.
Patent Information
- Application Number
- CN202411552936.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-01
AI Technical Summary
Existing ultraviolet curing resins rely on non-renewable resources and have a high environmental pollution, making it difficult to meet the needs of modern industry for high-performance environmentally friendly materials.
Using rosin-based bio-based materials, the synthesis of Malayan epoxy resin and hydroxyacrylate esters is introduced to a chain structure with a rigid structure of tricyclic diterpene and carbon-carbon double bonds to prepare a chain structure with high mechanical properties and environmental protection characteristics. Bio-based UV curing resin.
It improves the mechanical properties, crosslink density and thermal stability of ultraviolet curing resins, and realizes the preparation of green and environmentally friendly high-performance materials, suitable for adhesives, sealants and ultraviolet curing coatings and other fields.
Smart Images

Figure CN119431142A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a rosin-based bio-based ultraviolet light-curing resin and a preparation method and application thereof. Background Art
[0002] UV-curable materials have been widely used in modern industry due to their advantages of low energy consumption, fast curing speed, and low emission of volatile substances. In the existing technology, UV-curable resins are produced by non-renewable petroleum-based materials, which not only rely on non-renewable resources but also pollute the environment. As the concept of sustainable development has gained popularity, it is of practical significance to find alternative materials from renewable resources to manufacture UV-curable resins.
[0003] Rosin is a natural resin with a rigid tricyclic diterpene structure, which effectively increases the strength and glass transition temperature of the resin. Therefore, developing bio-based UV-curing resin using rosin-based epoxy resin as raw material is not only green and environmentally friendly, but also can meet the needs of modern industry for high-performance environmentally friendly materials. Summary of the invention
[0004] The first object of the present invention is to provide a rosin-based bio-based UV-curable resin to solve at least one of the above technical problems.
[0005] The second object of the present invention is to provide a method for preparing the above-mentioned rosin-based bio-based UV-curable resin to solve at least one of the above-mentioned technical problems.
[0006] The third object of the present invention is to provide an application of a rosin-based bio-based UV-curable resin in an adhesive, a sealant or a UV-curable coating to solve at least one of the above-mentioned technical problems.
[0007] A fourth object of the present invention is to provide a UV-curable composition to solve at least one of the above technical problems.
[0008] According to a first aspect of the present invention, the present invention provides a rosin-based bio-based UV-curable resin, and the structural formula of the rosin-based bio-based UV-curable resin is shown in formula (I):
[0009]
[0010] The rosin-based bio-based UV-curable resin of the present invention has a tricyclic diterpene rigid structure, a chain structure and a carbon-carbon double bond, and can improve the mechanical properties, flexibility and cross-linking density of the UV-curable resin. Experimental results show that after the rosin-based bio-based UV-curable resin of the present invention is UV-cured, the cross-linking degree inside the cured film is high, and it also has good tensile strength, hardness, adhesion performance and thermal stability.
[0011] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned rosin-based bio-based UV-curable resin, comprising the following steps:
[0012] 27-79 parts of maleic pine epoxy resin (MPA-ER), 15-77 parts of hydroxy acrylate, 0.05-0.75 parts of polymerization inhibitor and 0.07-1.53 parts of the first catalyst are mixed, heated to 80-130° C. in a nitrogen atmosphere, and then reacted until the acid value is less than 15 mgKOH / g to obtain;
[0013] The first catalyst is selected from at least one of N,N-dimethylbenzylamine, benzyltriethylammonium chloride, dibutyltin dilaurate, triethylamine and triphenylphosphine; and the inhibitor is selected from at least one of phenolic inhibitors and amine inhibitors.
[0014] The synthetic route of the rosin-based bio-based UV-curable resin is shown in formula (II):
[0015]
[0016] The preparation method of the rosin-based bio-based ultraviolet light-curing resin of the present invention uses the bio-based material maleic pine epoxy resin as a raw material, and is green and environmentally friendly. The epoxy group of the maleic pine epoxy resin is ring-opened under the attack of the hydroxyl group of the acrylate compound and the carbon-carbon double bond and chain structure of the acrylate compound are introduced to obtain a trifunctional light-curing resin having both a tricyclic diterpene rigid structure and a carbon-carbon double bond, which can improve the crosslinking density and rigid structure content of the light-curing resin, and the preparation method is simple.
[0017] In some embodiments, when preparing a rosin-based bio-based UV-curable resin, the amount of maleic pine epoxy resin can be 31-69 parts by weight, the amount of hydroxyacrylate can be 15-65 parts, the amount of inhibitor can be 0.05-0.69 parts, and the amount of catalyst can be 0.15-1.33 parts.
[0018] In some embodiments, the phenolic polymerization inhibitor may be selected from at least one of dinoseb, hydroquinone, and p-tert-butylcatechol, and the amine polymerization inhibitor may be diethylhydroxylamine.
[0019] In some embodiments, the maleic pine epoxy resin is prepared by the following steps:
[0020] After heating maleopimaric anhydride (MPA) and epichlorohydrin to dissolve into a homogeneous phase, a quaternary ammonium salt catalyst is added, and the reaction is carried out at 80-130° C. until the acid value is less than 1 mgKOH / g, and then the temperature is reduced to 50-90° C., sodium hydroxide is added, and the reaction is carried out until the pH value no longer decreases, and the epichlorohydrin is removed by distillation under reduced pressure to obtain the product.
[0021] The synthetic route of maleic pine epoxy resin is shown in formula (III):
[0022]
[0023] In some embodiments, the quaternary ammonium salt catalyst may be selected from at least one of tetrabutylammonium bromide and benzyltriethylammonium chloride.
[0024] In some embodiments, when preparing maleopimaric epoxy resin, the amount of maleopimaric anhydride used can be 27-79 parts by weight, the amount of epichlorohydrin used can be 165-225 parts, the amount of tetrabutylammonium bromide used can be 0.13-1.50 parts, and the amount of sodium hydroxide used can be 8-33 parts.
[0025] In other embodiments, when preparing maleopimaric epoxy resin, the amount of maleopimaric anhydride can be 35-69 parts, the amount of epichlorohydrin can be 175-205 parts, the amount of tetrabutylammonium bromide can be 0.15-1.25 parts, and the amount of sodium hydroxide can be 11-29 parts, based on parts by weight.
[0026] In some embodiments, the treatment method of reduced pressure distillation is to perform reduced pressure distillation at a temperature of 60-70° C. and a pressure of 120-150 Pa.
[0027] In some embodiments, the reaction time until the pH value no longer decreases can be 2-5 hours.
[0028] In some embodiments, hydroxy acrylate (HEMMA) is prepared by the following steps:
[0029] Mix hydroxyethyl methacrylate (HEMA), maleic anhydride (MA) and a polymerization inhibitor, and react them in a nitrogen atmosphere at a temperature of 80-130° C. for 3.5-8.5 hours to obtain the product.
[0030] The synthetic route of hydroxy acrylate is shown in formula (IV):
[0031]
[0032] In some embodiments, when preparing hydroxy acrylate, the amount of hydroxyethyl methacrylate can be 33-77 parts, the amount of maleic anhydride can be 19-59 parts, and the amount of inhibitor can be 0.05-0.25 parts by weight.
[0033] In other embodiments, when preparing hydroxy acrylate, the amount of hydroxyethyl methacrylate can be 39-67 parts by weight, the amount of maleic anhydride can be 25-55 parts, and the amount of inhibitor can be 0.05-0.19 parts by weight.
[0034] According to a third aspect of the present invention, there is provided a use of a rosin-based bio-based UV-curable resin in an adhesive, a sealant or a UV-curable coating.
[0035] According to the fourth aspect of the present invention, a UV-curable composition is provided, which comprises, by weight, 41-191 parts of a rosin-based bio-based UV-curable resin, 11-57 parts of a reactive diluent, and 1-9 parts of a photoinitiator. The UV-curable composition of the present invention can be applied to the fields of adhesives, sealants, UV-curable coatings, and the like.
[0036] In some embodiments, the reactive diluent is selected from at least one of acrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, isobornyl acrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, and hydroxyacrylate. Hydroxyacrylate, which is a raw material for the reaction of rosin-based bio-based UV-curable resin, can also be used as a reactive diluent to reduce the raw materials required for preparing the UV-curable composition. The UV-curable composition that meets the target performance is prepared by controlling the amount of the reactive diluent.
[0037] In some embodiments, the photoinitiator is selected from at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, hydroxycyclohexane phenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and benzophenone.
[0038] In some embodiments, the amount of the photoinitiator used is 2-4% of the total weight of the reactive diluent and the rosin-based bio-based UV-curable resin.
[0039] In some embodiments, the photocuring method of the rosin-based bio-based UV-curable resin composition is to mix the rosin-based bio-based UV-curable resin with a photoinitiator and crosslink under UV light with a wavelength of 300-400 nm for 2-5 minutes.
[0040] The beneficial effects of the present invention are:
[0041] The rosin-based bio-based UV-curable resin of the present invention is a trifunctional photocurable resin having a tricyclic diterpene rigid structure and a chain structure containing a carbon-carbon double bond, and its cured film has good mechanical properties and a high crosslinking density;
[0042] The cured film of the rosin-based bio-based UV-curable resin of the present invention has a tensile strength of not less than 63.45 MPa, an elongation at break of not less than 4.45%, a gel fraction of up to 95.52%, an adhesion of up to 2.85 MPa, a carbon residue rate of up to 6.73%, and a pencil hardness of up to 5H. It has excellent mechanical properties, adhesion properties and thermal stability, and can be used to prepare adhesives, sealants or UV-curable coatings;
[0043] The rosin-based bio-based ultraviolet curing resin of the present invention is prepared from bio-based materials, has a simple preparation method, and can also reduce dependence on non-renewable resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 It is the Fourier transform infrared spectrum of formula (II) to (IV) of the present invention. DETAILED DESCRIPTION
[0045] The present invention is further described in detail below in conjunction with the accompanying drawings, but the embodiments of the present invention are not limited thereto. The raw materials and reagents involved in the following examples can all be obtained from commercial channels.
[0046] Example 1
[0047] 50.00g of MPA and 185.00g of epichlorohydrin were added to a three-necked flask equipped with a stirring device, a condenser and a thermometer, heated to dissolve into a homogeneous phase, and then 2.35g of tetrabutylammonium bromide was added. The reaction system was reacted at 110°C until the acid value was less than 1mgKOH / g, then cooled to 70°C, 15g of sodium hydroxide was added, and then reacted for 3h until the pH value of the system no longer decreased, filtered, and the filtrate was washed with deionized water until neutral, and vacuum distilled at a temperature of 65°C and a pressure of 120-150Pa to recover excess epichlorohydrin to obtain a yellow transparent first reaction product weighing 58.60g.
[0048] 52.10 g HEMA, 39.20 g MA and 0.18 g hydroquinone were added into a three-necked flask with a stirring device, a condenser and a thermometer. In a nitrogen atmosphere, the reaction system was first heated to 70°C in an oil bath and stirred until the MA solid melted. The temperature was then raised to 100°C and the reaction was carried out for 5 h to obtain a second reaction product, which was a light yellow transparent liquid and 37.52 g was weighed.
[0049] The first reaction product obtained above, 18.14 g of the second reaction product, 0.76 g of N,N-dimethylbenzylamine and 0.15 g of hydroquinone were added to a three-necked flask equipped with a stirring device, a condenser and a thermometer, and stirred and reacted at 105° C. in a nitrogen atmosphere for 5 hours until the acid value was lower than 15 mgKOH / g. The mixture was cooled to room temperature, 17.58 g of the second reaction product was added, and the mixture was mixed evenly to obtain a final product, which was a light orange-red transparent solid.
[0050] The maleopimaric anhydride ( Figure 1 MPA line in), the first reaction product ( Figure 1 MPA-ER line), hydroxyethyl methacrylate ( Figure 1 HEMA line in), the second reaction product ( Figure 1 HEMMA line in) and the final product ( Figure 1 The MPA-ER-HEMMA line in the sample was used for infrared spectroscopy detection, and the detection results are shown in Figure 1 As shown. Figure 1 It can be seen that MPA at 1704cm -1 、1775cm -1 and 1844cm -1 The characteristic absorption peak attributed to the anhydride structure appeared; while the peak of MPA-ER was 1704cm -1 、1775cm -1 and 1844cm -1 The anhydride structure peak disappeared and the peak at 1735cm -1 The characteristic absorption peak attributed to the ester group appeared at 756 cm -1 、846cm -1 and 908cm -1 The characteristic peak of epoxy group (Epoxy) appears in the fingerprint area, indicating that MPA and epichlorohydrin have undergone esterification reaction to generate ester group. -1 The characteristic peaks attributed to hydroxyl groups appear around 1723 cm-1, which may be the hydroxyl peaks of the intermediate products of the reaction of formula (III) that did not participate in the ring-closing reaction and the hydroxyl peaks of the residual carboxyl groups of MPA. -1 and 1633cm -1 The characteristic peaks of 3500 cm-1 are attributed to the ester carbonyl group and the carbon-carbon double bond. -1 The characteristic peak of HEMMA is attributed to hydroxyl groups; -1 A new characteristic peak of carbon-carbon double bond appears at 2500-3400cm –1 A broad carboxyl peak appears, and at 3500 cm -1The characteristic absorption peak attributed to the hydroxyl group at 3521 cm-1 basically disappeared, indicating that the hydroxyl group of HEMA reacted with MA to form a new carbon-carbon double bond through Diels-Alder reaction. -1 The intensity of the characteristic absorption peak attributed to hydroxyl groups at 1728 cm-1 was significantly enhanced compared with that of MPA-ER, while the broad carboxyl peak and the characteristic peak of epoxy groups at the fingerprint region disappeared. This is because the epoxy groups of MPA-ER and the carboxyl groups of HEMMA undergo a ring-opening reaction to generate hydroxyl groups. The absorption peaks of the ester carbonyl group and carbon-carbon double bond originally belonging to HEMMA moved to 1728 cm-1, respectively. -1 and 1638cm -1 , 816cm -1 The characteristic peaks are attributed to the carbon-carbon double bond of HEMMA, indicating that the epoxy group of MPA-ER and the carboxyl group of HEMMA undergo a ring-opening reaction to generate hydroxyl groups, and the final product MPA-ER-HEMMA has a carbon-carbon double bond structure.
[0051] Example 2
[0052] The difference between this embodiment and embodiment 1 is that 44.79 g of the prepared second reaction product is weighed, 58.60 g of the first reaction product, 27.21 g of the second reaction product, 0.76 g of N,N-dimethylbenzylamine and 0.17 g of hydroquinone are added into a three-necked flask equipped with a stirring device, a condenser and a thermometer, and the mixture is stirred and reacted at 105° C. for 5 h in a nitrogen atmosphere until the acid value is lower than 15 mgKOH / g, the mixture is cooled to room temperature, 17.58 g is added, and the mixture is mixed uniformly to obtain a final product, which is a light orange-red transparent solid.
[0053] Example 3
[0054] The difference between this embodiment and embodiment 1 is that 53.86 g of the prepared second reaction product is weighed, 58.60 g of the first reaction product, 36.28 g of the second reaction product, 0.95 g of N, N-dimethylbenzylamine and 0.19 g of hydroquinone are added into a three-necked flask equipped with a stirring device, a condenser and a thermometer, and the mixture is stirred and reacted at 105° C. for 5 h in a nitrogen atmosphere until the acid value is lower than 15 mgKOH / g, and the mixture is cooled to room temperature, 17.58 g of the second reaction product is added, and the mixture is mixed uniformly to obtain a final product, which is a light orange-red transparent solid.
[0055] Example 4
[0056] The present embodiment provides a method for preparing a rosin-based bio-based UV-curable resin. The difference between the present embodiment and embodiment 1 is that 60.93 g of the prepared second reaction product is weighed, 58.60 g of the first reaction product, 43.35 g of the second reaction product, 1.02 g of N,N-dimethylbenzylamine and 0.20 g of hydroquinone are added to a three-necked flask equipped with a stirring device, a condenser and a thermometer, and the mixture is stirred and reacted at 105° C. for 5 h in a nitrogen atmosphere until the acid value is lower than 15 mgKOH / g, and the mixture is cooled to room temperature, 17.58 g of the second reaction product is added, and the mixture is mixed evenly to obtain a final product, which is a light orange-red transparent solid.
[0057] Example 5
[0058] The difference between this embodiment and embodiment 1 is that 81.07 g of the prepared second reaction product is weighed, 58.60 g of the first reaction product, 63.49 of the second reaction product, 1.22 g of N,N-dimethylbenzylamine and 0.24 g of hydroquinone are added into a three-necked flask equipped with a stirring device, a condenser and a thermometer, and the mixture is stirred and reacted at 105° C. for 5 h in a nitrogen atmosphere until the acid value is lower than 15 mgKOH / g, and the mixture is cooled to room temperature, 17.58 g of the second reaction product is added, and the mixture is mixed uniformly to obtain a final product, which is a light orange-red transparent solid.
[0059] Embodiments 6 to 14
[0060] The difference between Examples 6 to 14 and Example 1 is that when preparing the first reaction product, the added catalyst and the amount are different; when preparing the final product, the final product catalyst and the amount, the active diluent and the amount are different, as shown in Table 1.
[0061] Table 1 Selection and dosage of various reagents in Example 1 and Examples 6 to 14
[0062]
[0063] Embodiments 15 to 19
[0064] The difference between Examples 15 to 19 and Example 1 is that the weight of the first reaction product, the weight of the second reaction product, the selection of inhibitor and the amount of inhibitor added twice are different, as shown in Table 2.
[0065] Table 2 The mass of the first reaction product, the mass of the second reaction product, the inhibitor and the amount of the two additions in Example 1 and Examples 15 to 19
[0066]
[0067]
[0068] Embodiment 20
[0069] 41 g of the final product prepared in Example 1 was mixed with 5 g of 2-hydroxy-2-methyl-1-phenyl-1-propanone to obtain a UV-curable composition.
[0070] Examples 21 to 27
[0071] The difference between Examples 21 to 27 and Example 20 lies in the different amounts of final products, the selection of photoinitiators, and the amounts of photoinitiators used, as shown in Table 3.
[0072] Table 3 Composition of UV-curable compositions of Examples 20 to 27
[0073]
[0074] Comparative Example 1
[0075] 50.00 g of MPA and 185.00 g of epichlorohydrin were added to a three-necked flask equipped with a stirring device, a condenser and a thermometer, heated to dissolve into a homogeneous phase, and then 2.35 g of tetrabutylammonium bromide was added. The reaction system was reacted at 110° C. until the acid value reached below 1 mgKOH / g, then cooled to 70° C., 15 g of sodium hydroxide was added, and then reacted for 3 h until the pH value of the system no longer decreased, and NaCl was removed by filtration. The filtrate was washed with water until it was neutral, and the excess epichlorohydrin was recovered by reduced pressure distillation at a temperature of 65° C. and a pressure of 120-150 Pa to obtain MAP-ER;
[0076] 58.60 g of MPA-ER, 11.46 g of acrylic acid, 0.70 g of N,N-dimethylbenzylamine and 0.14 g of hydroquinone were added into a three-necked flask equipped with a stirring device, a condenser and a thermometer, reacted at 100 ° C for 5 h in a nitrogen atmosphere, cooled to room temperature, 17.58 g of acrylic acid was added, and mixed evenly to obtain MPA-ER-AA.
[0077] It was observed that MPA-ER-AA was a brown transparent solid.
[0078] Comparative Example 2
[0079] 52.10 g HEMA, 39.20 g MA and 0.18 g hydroquinone were added into a three-necked flask with a stirring device, a condenser and a thermometer. In a nitrogen atmosphere, the reaction system was first heated to 70°C in an oil bath, stirred until the MA solid melted, and then heated to 100°C and reacted for 5 h to obtain HEMMA.
[0080] 50.00 g of soybean oil triglycidyl ester (ESO), 43.50 g of HEMMA, 0.94 g of N,N-dimethylbenzylamine and 0.19 g of hydroquinone were added into a three-necked flask equipped with a stirring device, a condenser and a thermometer, stirred at 105 ° C for 5 h in a nitrogen atmosphere until the acid value was lower than 15 mgKOH / g, cooled to room temperature, 15.00 g of HEMMA was added, and mixed well to obtain ESO-HEMMA.
[0081] ESO-HEMMA was observed to be a light red transparent solid.
[0082] Comparative Example 3
[0083] 52.10 g HEMA, 39.20 g MA and 0.18 g hydroquinone were added into a three-necked flask with a stirring device, a condenser and a thermometer. In a nitrogen atmosphere, the reaction system was first heated to 70°C in an oil bath, stirred until the MA solid melted, and then heated to 100°C and reacted for 5 h to obtain HEMMA.
[0084] 45.40 g of epoxy resin E-44, 45.60 g of HEMMA, 0.84 g of N,N-dimethylbenzylamine and 0.17 g of hydroquinone were added to a three-necked flask equipped with a stirring device, a condenser and a thermometer, and stirred at 105 ° C for 5 h in a nitrogen atmosphere until the acid value was lower than 15 mgKOH / g. After cooling to room temperature, 13.62 g of HEMMA was added and mixed evenly to obtain a UV-curable resin.
[0085] Upon observation, the UV-curable resin was a light yellow transparent solid.
[0086] Experimental Example 1
[0087] In this experimental example, the cured films of the rosin-based bio-based UV-curable resin prepared in Examples 1-5 and Comparative Example 1, and the UV-curable resin prepared in Comparative Examples 2-3 were tested for plastic tensile properties, gel fraction, adhesion, pencil hardness, and thermogravimetric properties, and the results are shown in Table 4.
[0088] The method for preparing the cured film is to mix the rosin-based bio-based UV-curable resin prepared in Examples 1-5 and Comparative Example 1, and the UV-curable resin prepared in Comparative Examples 2-3, respectively, with a photoinitiator 1173 in an amount of 3% of the total mass of the UV-curable resin, and then perform UV curing for 3 minutes in UV light with a wavelength of 365 nm.
[0089] The cured films prepared from the rosin-based bio-based UV-curable resins of Examples 1-5 are sequentially recorded as F1, F2, F3, F4, and F5, the cured film of the rosin-based bio-based UV-curable resin of Comparative Example 1 is recorded as F6, and the cured films of the UV-curable resins of Comparative Examples 2 and 3 are recorded as F7 and F8, respectively. F1 to F8 are the samples used in each test of this experimental example.
[0090] 1. Plastic tensile properties test
[0091] The plastic tensile properties of samples F1 to F8 were tested using Shimadzu's AGS-X 1kN universal tester. The dumbbell-shaped sample specifications refer to GB / T 1040.2-2006, and the crosshead speed is 1mm min. -1 In order to ensure the accuracy of the test results, each sample was tested three times and the test results were averaged.
[0092] 2. Gel rate test
[0093] Take 0.5g of samples F1 to F8 and immerse them in 10mL acetone, soak them at room temperature for 48h, and then dry them in an oven at 60℃ to constant weight. In order to test the accuracy of the results, each sample was tested three times and the test results were averaged. The gel fraction (GC) was calculated according to the following formula:
[0094]
[0095] Among them, W a W0 is the weight of the cured film after immersion and drying, and W0 is the original weight of the cured film.
[0096] 3. Adhesion Test
[0097] Using a 250μm four-sided film applicator, take 2-5g of the rosin-based bio-based UV-curable resin of Examples 1-5 and Comparative Example 1, and the UV-curable resin of Comparative Example 2-3, respectively, and mix them evenly with the photoinitiator 1173 in an amount of 3% of the total mass of the UV-curable resin, then evenly apply the mixture on a galvanized iron plate, UV-curing for 3min in UV light with a wavelength of 365nm, and then fix the ingot on the cured film with glue, and after standing for 24h, use a fully automatic pull-off adhesion tester for testing, the instrument range is: 0.7-20MPa. In order to test the accuracy of the results, each sample was tested three times, and the test results were averaged.
[0098] 4. Pencil hardness test
[0099] The pencil hardness of the cured films of F1 to F8 was tested according to GB / T 6739-2022 "Determination of film hardness by pencil method for paints and varnishes". In order to ensure the accuracy of the test results, each sample was tested three times and the test results were averaged.
[0100] 5. Thermogravimetric test
[0101] Thermogravimetric analysis of the cured films of F1 to F8 was performed using a Netzsch STA 449C thermal analyzer. The temperature range required for the thermogravimetric test of the samples was set to 35-800°C, and the heating rate was 10°C min -1 During the test, the nitrogen environment was maintained and the nitrogen introduction rate was 20 mL min -1 To test the accuracy of the results, each sample was measured three times and the average value was taken.
[0102] The samples were subjected to thermogravimetric analysis, and the thermal degradation temperature (T 10% ), 50% thermal degradation temperature (T 50% ), and the carbon residue rate at 800℃.
[0103] Table 4 Comprehensive performance test results of cured film
[0104]
[0105] As can be seen from Table 4, the tensile strength of the cured films of the rosin-based bio-based UV-curable resin of Examples 1-5 can reach up to 71.23 MPa, and the elongation at break is up to 9.55%, indicating that the cured films of the rosin-based bio-based UV-curable resin of the present invention have good mechanical properties. The best result of the adhesion test is 2.85 MPa, indicating that the rosin-based bio-based UV-curable resin of the present invention has good adhesion properties after being cured into a film. From the results of the thermogravimetric test, in the cured films of each embodiment, T 10% and T 50% The highest temperatures can reach 308.53°C and 411.82°C respectively, and the highest carbon residue rate can reach 6.73%, indicating that the cured film of the rosin-based bio-based UV-curable resin of the present invention has good thermal stability. The gel rate test results show that the gel rate of the cured film of the rosin-based bio-based UV-curable resin of Examples 1-5 can reach up to 95.52%, indicating that the cross-linking density of the cured film of the rosin-based bio-based UV-curable resin of the present invention is relatively high. In addition, the pencil hardness test results show that the pencil hardness of the cured film of the rosin-based bio-based UV-curable resin of Examples 1-5 is between 3H and 5H, indicating that the cured film of the rosin-based bio-based UV-curable resin of the present invention has good hardness.
[0106] Below, the comprehensive performance test results of the cured film of the rosin-based bio-based UV-curable resin of Examples 1-5 are used to illustrate the effect of the HEMMA content on the various properties of the cured film. Specifically, at the beginning, as the HEMMA content increases, the various performance test results of the cured film of the rosin-based bio-based UV-curable resin of the present invention improve. Among them, as the HEMMA content increases, the tensile strength increases from 63.45MPa to 71.23MPa, and the elongation at break increases from 4.45% to 9.55%, indicating that the amount of HEMMA selected brings about a significant improvement in the flexibility and mechanical properties of the rosin-based bio-based UV-curable resin. This is because when MPA-ER reacts with HEMMA, a side chain structure containing carbon-carbon double bonds is introduced, which significantly improves the curing efficiency and cross-linking density during UV curing. After reaching the peak value, the test results of various properties decreased with the increase of HEMMA content. The reason may be that the chain structure of HEMMA will react with the hydroxyl group after the ring opening of MPA-ER, and the relative content of the rigid structure of the product will decrease, resulting in the network structure of the rosin-based bio-based UV-curable resin being not stable enough. In addition, compared with the comprehensive performance test results of the cured film of the rosin-based bio-based UV-curable resin (Comparative Example 1) without HEMMA, the various properties of the cured films of the rosin-based bio-based UV-curable resin of Examples 1-5 are significantly improved. Therefore, the present invention can prepare a rosin-based bio-based UV-curable resin that meets the performance requirements by selecting the amount of hydroxyacrylate.
[0107] By comparing the performance test results of the cured films of the rosin-based bio-based UV-curable resin of Examples 1-5 with the cured films of the UV-curable resin of Comparative Examples 2 and 3, it is found that the performance of the cured films of the rosin-based bio-based UV-curable resin of the present invention is significantly better than that of the cured films of the UV-curable resin of Comparative Example 2, indicating that the effect of the HEMMA-modified MPA-ER of the present invention is better than that of the HEMMA-modified epoxidized soybean oil ESO. At the same time, the mechanical property test results of the cured films of the rosin-based bio-based UV-curable resin of the present invention are close to those of the cured films of the UV-curable resin of Comparative Example 3. The cured films of the UV-curable resin of Comparative Example 3 show a more excellent effect in the thermal stability performance test, because the thermal decomposition temperature of the aromatic benzene ring in the E-44 epoxy resin is higher than the thermal decomposition temperature of the aliphatic hydrogen phenanthrene ring in the MPA-ER. In addition, the cured films of the rosin-based bio-based UV-curable resin of some embodiments have better elongation at break, gel rate, adhesion and pencil hardness test results than those of Comparative Example 3, indicating that the cured films of the rosin-based bio-based UV-curable resin obtained by using HEMMA-modified bio-based MPA-ER of the present invention have similar mechanical properties to those of the UV-curable resin cured films obtained by using HEMMA-modified petroleum-based epoxy resin E-44, and some performance tests show better results, indicating that the present invention has found a good bio-based alternative material for UV-curable resin.
[0108] In summary, the rosin-based bio-based UV-curable resin of the present invention has both the rigid structure unique to maleic maritime pine epoxy resin and the chain structure containing carbon-carbon double bonds, which is not only beneficial to improving the rigid structure content, cross-linking density and flexibility of the cured film of the rosin-based bio-based UV-curable resin, but also enables the cured film of the rosin-based bio-based UV-curable resin of the present invention to have good mechanical properties, adhesion properties and thermal stability.
[0109] The preparation method of the rosin-based bio-based UV-curable resin of the present invention comprises the following steps: firstly modifying maleic pine epoxy resin with hydroxy acrylate, and introducing a chain structure containing a carbon-carbon double bond into the maleic pine epoxy resin. The preparation method is simple, and uses bio-based materials as raw materials, which is green and environmentally friendly. The rosin-based bio-based UV-curable resin prepared by the preparation method has a tensile strength of 71.23MPa, a gel rate of 95.52%, an adhesion of 2.85MPa, a carbon residue rate of 6.73%, and a pencil hardness of 5H after UV-curing film formation. In addition, the comprehensive performance of the cured film of the rosin-based bio-based UV-curable resin of the present invention is significantly better than that of the cured film of the bio-based UV-curable resin of acrylate-modified epoxidized soybean oil; the tensile strength of the cured film of the rosin-based bio-based UV-curable resin is close to that of the UV-curable resin obtained by HEMMA-modified petroleum-based epoxy resin E-44, and the former can obtain better test results in adhesion, gel rate and pencil hardness tests.
[0110] The above are only some embodiments of the present invention. For those skilled in the art, several modifications and improvements can be made without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A rosin-based bio-based UV-curable resin, characterized in that: Its structural formula is shown in formula (I):
2. The method for preparing the rosin-based bio-based UV-curable resin according to claim 1, characterized in that: 27-79 parts of maleic pine epoxy resin, 15-77 parts of hydroxy acrylate, 0.05-0.75 parts of polymerization inhibitor and 0.07-1.53 parts of the first catalyst are mixed, heated to 80-130° C. in a nitrogen atmosphere, and then reacted until the acid value is less than 15 mgKOH / g to obtain; The first catalyst is selected from at least one of N,N-dimethylbenzylamine, benzyltriethylammonium chloride, dibutyltin dilaurate, triethylamine and triphenylphosphine; and the inhibitor is selected from at least one of phenolic inhibitors and amine inhibitors.
3. The method for preparing the rosin-based bio-based UV-curable resin according to claim 2, characterized in that: The phenolic polymerization inhibitor is selected from at least one of dinoseb, hydroquinone and p-tert-butylcatechol, and the amine polymerization inhibitor is diethylhydroxylamine.
4. The method for preparing the rosin-based bio-based UV-curable resin according to claim 2 or 3, characterized in that: The maleic pine epoxy resin is prepared by the following steps: After heating and dissolving maleopimaric anhydride and epichlorohydrin into a homogeneous phase, adding a quaternary ammonium salt catalyst, reacting at 80-130°C until the acid value is less than 1 mgKOH / g, cooling to 50-90°C, adding sodium hydroxide, reacting until the pH value no longer decreases, and removing epichlorohydrin by reduced pressure distillation at a temperature of 60-70°C and a pressure of 150-160Pa to obtain; Wherein, in parts by weight, the amount of maleopimaric anhydride is 27-79 parts, the amount of epichlorohydrin is 165-225 parts, the amount of quaternary ammonium salt catalyst is 0.13-1.50 parts, and the amount of sodium hydroxide is 8-33 parts.
5. The method for preparing the rosin-based bio-based UV-curable resin according to claim 4, characterized in that: The quaternary ammonium salt catalyst is selected from at least one of tetrabutylammonium bromide and benzyltriethylammonium chloride.
6. The method for preparing the rosin-based bio-based UV-curable resin according to claim 2 or 3, characterized in that: The hydroxyacrylate is prepared by the following steps: Mix hydroxyethyl methacrylate, maleic anhydride and a polymerization inhibitor, and react in a nitrogen atmosphere at a temperature of 80-130° C. for 3.5-8.5 hours to obtain; Wherein, in parts by weight, the amount of hydroxyethyl methacrylate is 33-77 parts, the amount of maleic anhydride is 19-59 parts, and the amount of the polymerization inhibitor is 0.05-0.25 parts.
7. Use of the rosin-based bio-based UV-curable resin according to claim 1 in adhesives, sealants or UV-curable coatings.
8. A UV-curable composition, characterized in that: In parts by weight, it comprises 41-191 parts of the rosin-based bio-based UV-curable resin according to claim 1, 11-57 parts of a reactive diluent, and 1-9 parts of a photoinitiator; Wherein, the active diluent is selected from at least one of acrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, isobornyl acrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, and hydroxyacrylate; The photoinitiator is selected from at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, hydroxycyclohexane phenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide and benzophenone.
Citation Information
Patent Citations
Rosin epoxy resin and preparation method thereof
CN102329309A
Silicon-containing flame-retardant rosin-based polyol, and preparation method and application thereof
CN106543426A
Synthesis method of trifunctional rosin-based epoxy resin
CN110172135A
Preparation method of solvent-free two-component epoxy adhesive
CN116836666A
Cited By
Bio-based modified epoxy resin composition and application thereof
CN120737545A
Multifunctional rosin-based reactive diluent as well as preparation method and application thereof
CN121135614A
Multifunctional rosin-based reactive diluents, methods of making and using the same
CN121135614B
Organic silicon modified rosin-based polyurethane material as well as preparation method and application thereof
CN121673514A